Procedimentos Periciais em Foco - Bruni, Aline Thaís; Pinheiro Silva, Adelino; Telles, Bruno; Rodrigues Filho, Claudemir; de Andrade Gomes, Juliano; de Medeiros Tocantins, Rogério (Revista Brasileira de Criminalística, 2019)
Editorial do Volume 8, número 1.